Patterns of Thermal Sensitivity and Sex-Specificity of Courtship Behavior Differs Between Two Sympatric Species of Enchenopa Treehopper - Macchiano, Anthony; Sasson, Daniel A.; Leith, Noah T.; Fowler-Finn, Kasey D. (Frontiers in Ecology and Evolution, 2019)
Predicting how insects will react to future thermal conditions requires understanding how temperature currently affects insect behavior, from performance traits to those involved in mating and reproduction. Many reproductive behaviors are thermally-sensitive, but little is known how temperature affects the behaviors used to find mates and coordinate mating. Here, we investigate how temperature influences courtship activity in two sympatric species of Enchenopa treehoppers (Hemiptera: Membracidae). Enchenopa use substrate-borne vibrational signals exchanged in male-female duets to facilitate pair formation prior to mating. In a controlled laboratory setting, we assessed the likelihood of males and females to produce courtship signals across a range of ecologically relevant temperatures. We found that changes in courtship activity across temperatures differed between the two species. We also found sex differences within species: in one species males were more likely to signal at higher temperatures, while in the other species females were more likely to signal at higher temperatures. Our results suggest that sex-specific responses to temperature may constrain mating to narrower ranges of temperatures. Furthermore, sympatric species may respond differently to changes in thermal variation despite sharing similar climactic history.